Manajemen Peserta Didik di PKBM Berbasis Alam Studi pada Sanggar Anak Alam (SALAM) - Gunarti Ika Pradewi; Wiwik Wijayanti; Sukowati Sukowati (Universitas Kristen Satya Wacana, 2019)
This research aims to describe the pupil personnel administration conducted in Sanggar Anak Alam (SALAM). SALAM is a form of Teaching-learning activity centre which is based in nature. The method used in this research was qualitative research. The data were collected through the interview, observation, and documental study. The results of this research are: (1) in the recruitment process of students, SALAM gets many helps from media to promote their service, moreover the accountability of the process and the funding of education which are conducted become the essential thing to obtain parents’ trust and make them enrol their children at SALAM. (2) Related to the grouping and guiding: (a) the number of students in each group only consists of about 15 students, (b) the academic and non-academic guiding are based on four pillars of education which consists of food, health, environment, and social-culture, (c) the guiding of interest is conducted through the interest class, (d) there is student guiding through the forum of parents. (3) The evaluation of students can be conducted every time, but the implementation is different for each student. It occurs because the learning method used is research method. Whereas, for the report of students’ learning achievement, there are three methods used, they are: students’ learning process note based on the research for one semester, students’ attitude notein the learning process for one semester, and students’ body skill note in the learning process for onesemester.